Mitochondrial DNA sequence heteroplasmy in the Grand Duke of Russia Georgij Romanov establishes the authenticity of the remains of Tsar Nicholas II - Ivanov, P L; Wadhams, M J; Roby, R K; Holland, M M; Weedn, V W; Parsons, T J (Nature genetics, 1996)
In 1991, nine sets of skeletal remains were excavated from a mass grave near Yekaterinburg, Russia which were believed to include the Russian Tsar Nicholas II, the Tsarina Alexandra, and three of their daughters. Nuclear DNA testing of the remains verified such a family group, and mitochondrial DNA (mtDNA) sequences of the presumed Tsarina matched a known maternal relative, Prince Philip. mtDNA sequences from bone of the presumed Tsar matched two living maternal relatives except at a single position, where the bone sample had a mixture of matching (T) and mismatching (C) bases. Cloning experiments indicated that this mixture was due to heteroplasmy within the Tsar; nevertheless, the 'mismatch' fueled a lingering controversy concerning the authenticity of these remains. As a result, the official final report on the fate of the last Russian Royals has been postponed by Russian authorities pending additional, convincing DNA evidence. At the request of the Russian Federation government, we analysed the skeletal remains of the Tsar's brother Georgij Romanov in order to gain further insight into the occurrence and segregation of heteroplasmic mtDNA variants in the Tsar's maternal lineage. The mtDNA sequence of Georgij Romanov, matched that of the putative Tsar, and was heteroplasmic at the same position. This confirms heteroplasmy in the Tsar's lineage, and is powerful evidence supporting the identification of Tsar Nicholas II. The rapid intergenerational shift from heteroplasmy to homoplasmy, and the different heteroplasmic ratios in the brothers, is consistent with a 'bottleneck' mechanism of mtDNA segregation.